Assistive technology: choosing the right tool for the right job. - Gamble MJ; Dowler DL; Orslene LE (Journal of Vocational Rehabilitation, 2006)
Rehabilitation professionals are often required to make decisions about the benefits of using assistive technology in the workplace. Knowledge of current resources and a systematic process for identifying and selecting AT increase the likelihood of successful consumer outcomes. Increased access to assistive technology has opened employment opportunities for many individuals with disabilities, but barriers to successful accommodation include inappropriate selection of AT and discontinuance of the implemented technology. This article presents a review of relevant literature on the use of workplace AT and describes a model for selecting appropriate assistive technology.